(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Amino acids are having important role in the foods and nutrients. Glycine has the major role and physical study of these glycine materials is essential. In the present study, triglycine formate and triglycine oxalate crystals were grown by slow evaporation method. The grown crystals were characterized by CHNS analysis and powder X-ray diffraction. CHNS results showed that all the elements are presented in the grown crystals with appropriate value. Powder X-ray diffraction pattern revealed that the grown crystals belong to monoclinic structure. Thermal parameters like Debye–Waller factor, mean-square amplitude of vibration and Debye temperature were determined using powder X-ray diffraction data. The thermal parameters of triglycine formate have lower than the triglycine oxalate single crystals.